On the influence of loudspeaker and microphone array geometries on the limits for listening room equalization in a spatial continuum - Schneider, Martin; Kellermann, Walter (AIA-DAGA Conference on Acoustics, 2013)
In audio reproduction, loudspeaker signals are often optimized to be ideally rendered under free-field conditions. In real reverberant listening rooms a listening room equalization (LRE) system may be used to improve to reproduction quality by removing the undesired reverberation. To this end, additional microphones are placed in the listening room and the resulting loudspeakerenclosure-microphone system (LEMS) is then identified to determine equalizing pre-filters for the loudspeaker signals. As the listener position may vary, an equalization in a spatially extended zone is desired as it was already considered in early work on LRE [1]. Later work involved systematically placed loudspeakers and microphones to improve the LRE in a spatially extended zone [2, 3]. It turned out that loudspeaker arrays used for wave field synthesis (WFS) [4] or Higher-Order Ambisonics (HOA) [5] allow for a sufficient control over the reproduced wave field to equalize a spatially extended zone in a corresponding frequency area. Microphone arrays designed for wave field analysis allow for a description of a wave field in an extended zone and are therefore attractive candidates to complement the WFS or HOA loudspeaker arrays in an LRE system. However, a spatially extended equalization can only be achieved for wave field components which may be measured and controlled at the same time. In this contribution, some combinations of differently shaped loudspeaker and microphone arrays are analyzed with respect to their suitability for LRE.